2021
DOI: 10.1111/jonm.13329
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress and affecting factors related to COVID‐19 pandemic of emergency nurses in Turkey

Abstract: COVID-19 is an infectious disease caused by a newly emerging coronavirus infection. A pandemic was announced by the World Health Organization (WHO) in March 2020 due to COVID-19 disease (WHO, 2020a;Li et al., 2020). Since the announcement of the COVID-19 pandemic, a total of 43 million COVID-19 cases have been reported globally, including approximately one million deaths. In Turkey, according to the latest data of the Ministry of Health, a total of 361 thousand COVID-19 cases, including 9,799 deaths, have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 26 publications
1
34
1
Order By: Relevance
“…An increased workload/job stress may have cascading adverse effects on relationships, appropriate service delivery and overall job performance among nurses (Cui et al., 2021 ; Gualano et al., 2021 ; Zare et al., 2021 ). The situation may even be worse when most nurses fear COVID‐19 due to the limited PPEs, and other uncertainties surrounding COVID‐19, and unavailability of a cure or definite treatment (Al Thobaity & Alshammari, 2020 ; Çınar et al., 2021 ; Zare et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…An increased workload/job stress may have cascading adverse effects on relationships, appropriate service delivery and overall job performance among nurses (Cui et al., 2021 ; Gualano et al., 2021 ; Zare et al., 2021 ). The situation may even be worse when most nurses fear COVID‐19 due to the limited PPEs, and other uncertainties surrounding COVID‐19, and unavailability of a cure or definite treatment (Al Thobaity & Alshammari, 2020 ; Çınar et al., 2021 ; Zare et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the study conducted by Said and El-Shafei to examine the job stress, job satisfaction, and intent to quit among nurses working in Egypt during the COVID-19 pandemic, they stated that three-quarters of the nurses had a high level of job stress [7]. In a study conducted by Çınar et al, to examine the perceived stress in nurses working in the emergency room during the pandemic in Turkey and the effect of the pandemic on stress, they determined that nearly half of the nurses experienced stress above average [14]. They also found that the factors significantly affecting the stress score of emergency room nurses were respiratory isolation, change in lifestyle, inability to access protective equipment, inadequate number of nurses in the unit, and risk of being infected with COVID-19 [14].…”
Section: Discussionmentioning
confidence: 99%
“…The research during past pandemics has shown that health care workers are more likely to develop postpandemic stress disorder (Lee et al, 2018;Tam et al, 2004). Increasing the number of staff, arranging the shift system, providing psychological counselling and guidance in the form of support services on online platforms or by phone, especially to relieve front-line nurses can alleviate the permanent effects of psychological difficulties (Çınar et al, 2021;Kang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Work intensity affects the efficiency and strength of the nurses. For this reason, it is important to continuously optimize the number of nurses and to arrange the shift systems in a way that provides adequate rest and nutrition in order to ensure the continuity of the workforce (Çınar et al, 2021;He et al, 2021;Kang et al, 2020;Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%